FIRST COMMEMORATION OF THE LITHUANIAN PRESS RESTORATION IN INDEPENDENT LITHUANIA IN 1929 - Janušauskaitė, Ida (Knygotyra, 2016)
The article is dedicated to researching the 25th anniversary of the restoration of free Lithuanian press in Latin characters, celebrated in 1929. The research is aimed at elucidating the initiators of celebrating the anniversary, finding out who the organizers were and how the celebration in question succeeded. The conducted research showed that the very first initiators were the Kaunas city intellectuals, who established the special committee, named Komitetas spaudos atgavimo 25-mečio minėjimui. The main members of the committee were widely known persons – Vaclovas Biržiška, Petras Ruseckas, Vincas Vileišis, Juozas Žiugžda and Balys Žygelis. The Committee started to spread the idea of the celebration. One of the most important publications published by the Committee was the P. Ruseckas Proclamation for the Society, which presented appropriate ways to commemorate the anniversary of free press. After all organizational procedures had been finalized, the Committee organized a great celebration on May 9th, 1929. As the Committee started to organize the anniversary, another organization emerged. On March 22nd, the Association of Lithuania’s Journalists separated from Writers’ Association. From the first day journalists decided to organize press anniversary celebration – The Press Ball. Aided by the right political wing, including the President of the Republic Antanas Smetona and the Prime Minister Augustinas Voldemaras, the Lithuanian journalists organized an even greater ceremony. It was held on May 18th, with the Prime Minister attending as an honourable guest and delivering an opening speech. During the ball, the journalists expressed an idea to publish four issues of a 4 page newspaper, covering the information about the ceremony and guests. Unfortunately, only 2 issues were published. However, it is difficult to compare these two celebrations, because the Committee had no political support and no financial foundation while the journalists were supported by the government. The two previously mentioned celebrations were held in Kaunas, but the idea to celebrate anniversary gradually spread in the whole country. Various organizations in smaller cities and even in the then occupied Vilnius organized celebrations. In the Šiauliai central city square, 4 Press Oaks were planted as a memorial of the period when press was prohibited. In Vilnius, the memorable part of the celebration was a huge exhibition with a great number of publications issued during the press prohibition times. Thus, a widely commemorated anniversary began a new traditional celebration.
Keywords: ...